Exercise as a Non-Pharmacological Therapeutic Strategy in Breast Cancer: An Umbrella Review of Systematic Reviews and Meta-Analyses - Hendawy, Mohamed; Abouzid, Mohamed; Alnajjar, Asmaa Zakria; Elnagar, Marwa; Rzk, Fayed Mohamed; Daniel, John Magdy; Elshazly, Heba; Saad, Mohamed Mahmoud (Journal of Medical Science, 2026)
Background. Breast cancer is the most prevalent cancer diagnosis and a leading cause of cancer-related mortality among women globally. Exercise has gained traction as a promising non-pharmacological strategy to manage cancer-related fatigue, pain, quality of life, anxiety, and depression. However, the current evidence regarding exercise's effects on breast cancer is heterogeneous, with variations in study designs, exercise modalities, and outcome measures. Therefore, this umbrella meta-analysis is conducted to synthesise more robust findings.Material and methods. Adhering to the PRIO and PRIO-harms guidelines, Eligible systematic reviews and meta-analyses published between January 2001 and December 2023 were identified from PubMed, Scopus, Web of Science, and the Cochrane Library. Using StataMP version 17, Outcomes are reported as standardised mean differences (SMD) with 95% confidence intervals (CI). A p-value ≤ 0.05 was considered statistically significant.Results. This umbrella review synthesised evidence from 44 systematic reviews, including 31 meta-analyses. These reviews encompassed 906 randomised controlled trials (RCTs) evaluating the effects of exercise interventions on various outcomes in breast cancer patients. Patients undergoing exercise programs demonstrated improvements in fatigue (SMD -0.26, 95% CI [-0.44, -0.08], p < 0.01), pain (SMD -0.65, 95% CI [-1.10, -0.19], p = 0.01), quality of life (SMD 0.28, 95% CI [0.21, 0.36], p < 0.01), and physical activity level (SMD 0.30, 95% CI [0.21, 0.39], p < 0.001). No significant effects were observed for anxiety (SMD 0.00, 95% CI [-0.62, 0.63], p = 1.00) or depression (SMD -0.45, 95% CI [-1.00, 0.10], p = 0.11).Conclusions. This umbrella meta-analysis provides evidence that exercise in breast cancer patients can reduce fatigue, enhance quality of life, improve physical function, and alleviate pain. However, the impact on depression and anxiety appears limited.
Keywords: cancer; exercise; CRF; systematic review; umbrella